Insulin and 5-Aminoimidazole-4-Carboxamide Ribonucleotide (AICAR) Differentially Regulate the Skeletal Muscle Cell Secretome - Alba Gonzalez-Franquesa; Lone Peijs; Daniel T. Cervone; Ceren Koçana; Juleen R. Zierath; Atul S. Deshmukh (Proteomes, 2021)
Skeletal muscle is a major contributor to whole-body glucose homeostasis and is an important endocrine organ. To date, few studies have undertaken the large-scale identification of skeletal muscle-derived secreted proteins (myokines), particularly in response to stimuli that activate pathways governing energy metabolism in health and disease. Whereas the AMP-activated protein kinase (AMPK) and insulin-signaling pathways have received notable attention for their ability to independently regulate skeletal muscle substrate metabolism, little work has examined their ability to re-pattern the secretome. The present study coupled the use of high-resolution MS-based proteomics and bioinformatics analysis of conditioned media derived from 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR—an AMPK activator)- and insulin-treated differentiated C2C12 myotubes. We quantified 858 secreted proteins, including cytokines and growth factors such as fibroblast growth factor-21 (Fgf21). We identified 377 and 118 proteins that were significantly altered by insulin and AICAR treatment, respectively. Notably, the family of insulin growth factor binding-proteins (Igfbp) was differentially regulated by each treatment. Insulin- but not AICAR-induced conditioned media increased the mitochondrial respiratory capacity of myotubes, potentially via secreted factors. These findings may serve as an important resource to elucidate secondary metabolic effects of insulin and AICAR stimulation in skeletal muscle.